PENGARUH LIKUIDITAS, LEVERAGE DAN PROFITABILITAS TERHADAP FINANCIAL DISTRESS (Z-SCORE) PERUSAHAAN PROPERTY, REAL ESTATE, DAN MANUFAKTUR PERIODE 2014-2016 - Eveline Kusuma; Sumani Sumani (Jurnal Manajemen, 2017)
This study aims to reexamine the influence of liquidity ratio, leverage ratio and profitability ratio on financial distress conducted on property, real estate and manufacturing companies listed on the Indonesia Stock Exchange period 2014-2016. This is because the property, real estate and manufacturing industries in the 2014-2016 period show symptoms of ups and downs as a result of economic movement in Indonesia. The research was conducted by measuring the level of financial distress formulated by Altman (1968) that is Z-score model, followed by calculating liquidity ratio represented by current ratio, leverage ratio represented by debt ratio and profitability ratio represented return on assets. Data processing using Eviews. The results obtained from this research is the ratio of leverage represented debt ratio, significantly have an effect to financial distress, while the other two ratios are not significant.